The impact of vitamin D3 administration and of high fat diet on oxidative stress and inflammation in experimentally induced polycystic ovary syndrome - Vulcan, Talida; Suciu, Tudor Sergiu; Lenghel, Lavinia Manuela; Toma, Vlad Alexandru; Decea, Nicoleta; Moldovan, Remus; Mitrea, Daniela-Rodica; Baldea, Ioana; Filip, Gabriela Adriana (Medicine and Pharmacy Reports, 2024)
Background. Polycystic ovary syndrome (PCOS) is commonly associated with obesity and may be exacerbated by the lack of vitamin D3. Aim. The study aimed to investigate the effects of vitamin D3 administration in female rats with PCOS and prolonged high fat diet (HFD). Methods. Forty-four female Wistar rats, 180-200 g, 10 weeks old, were randomly allocated into 2 groups (n=22) that received a single dose intramuscular injection of: sesame oil (group I), or estradiol valerate (5 mg) in sesame oil (group II). After 4 weeks, intraovarian cysts developed in group II, as evidenced by ultrasonography. In the next step, half of rats from each group received standard diet (SD) and the other half high fat diet, through oral gavage, for 17 weeks, the following groups being obtained: Control (SD), HFD, PCOS (PCOS+SD) and PCOS+HFD. Next, all the rats received, for 5 weeks, 500 UI/kg/day vitamin D3, through oral gavage. Lipid peroxidation was assessed through malondialdehyde level in the ovary and periovarian tissue and the inflammation was quantified in ovary by NFkB, pNFkB, NRF2 and SOD1 expressions. Ovaries from all groups were collected for histopathological analysis. Blood samples were taken to evaluate the basal insulin, triglycerides and total cholesterol levels throughout the experiment. Results. Both groups with PCOS recorded significant increases of malondialdehyde in ovaries (p<0.001) and in periovarian tissue, especially in PCOS+HFD (p<0.05), even after vitamin D3 administration. PCOS+HFD group treated with vitamin D3 showed a high degree of inflammation in ovarian histopathology but with decreased pNFkB expression (p<0.01) while PCOS group recorded an increased SOD1 expression (p<0.05). Additionally, vitamin D3 treatment attenuated the insulin level (p<0.001) in PCOS and in HFD groups and the total cholesterol level in PCOS+HFD group, but triglycerides recordings were without statistical significance (p>0.05). HFD induced inflammation in ovaries, evidenced histologically and through increases of COX2 expressions (p<0.05) without significant influences on oxidative stress and on cholesterol levels. Conclusions. Polycystic ovary syndrome is associated with oxidative stress and inflammation in the ovary tissue and in blood with increased levels of insulin, total cholesterol and triglycerides that might be partially mitigated by vitamin D3 oral administration.